The effect of acupressure on hope and self-efficacy of hemodialysis patients: a double-blind clinical trial - Mahnaz Kayyal; Ali Asghar Jesmi; Neda Mahdavifar; Raghayeh Javan; Mostafa Abdollahi; Ali Taj (Payesh)
Objective(s): Chronic kidney failure is considered as a life-threatening disease, and strengthening factors such as hope and self-efficacy improves the quality of life in these patients and also improves their self-care. Therefore, this study was conducted aiming to examine the effect of acupressure on hope and self-efficacy of patients undergoing hemodialysis treatment. Methods: This was a double-blind clinical trial that was conducted on 54 hemodialysis patients in Beshrouye and Tabas in Iran, in 2022. Patients were divided into three groups of control, intervention and sham (fake group) through permutation blocks. Data were collected with short cognitive questionnaire, demographic information, Harth's hope and Scherer's self-efficacy. In the acupressure intervention group during dialysis, in the sham group, acupressure was performed at a distance of 1-1.5 cm from the main points and under the control only thr usual care was offered. Data were analyzed using SPSS24 software. Results: The results showed that there was a statistically significant difference in the mean hope score among the investigated groups (P<0.001). Also, the mean self-efficacy score among the groups had a statistically significant difference (P<0.001). Conclusion: The results showed that acupressure was effective in increasing hope and self-efficacy of hemodialysis patients, and as an easy, cheap and simple method, it can be easily implemented by nurses and even patients themselves in the ward.